Analisis Penerimaan Aplikasi Buku Pelaut Online (BPO) Menggunakan Metode Technologi Acceptance Model (TAM) Pada Kantor Kesyahbandaran Dan Otoritas Pelabuhan - Naralia, Mirah; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2024)
The application buku pelaut online (bpo) is an application that makes it easy for users to obtain identity data, information on personal data sailing period, extension or replacement of seafater’ books so that all seafarer get digital services and a more secure system. There are still users who do not know the convenience and benefits that exist in the application. This study aims to analyze user acceptance of the online seaman book publishing application (BPO), using the technology acceptance model (TAM) method. This study uses there modified variables, namely Perceived ease of use (PEOU) and Perceived usefulness (PU) as independent variables while Acceptance of it as the dependent variables. This sampling technique uses the Probability sample technique with a cluster sampling approach whit a total 118 responden. Users data analysis technique using Statistical Package For The Social Science (SPSS) Applications. Thus if the value of the convenience and benefits factor increases, the user’a acceptance of the informatioan system will increases.